Genetic variability for key physiological traits in groundnut under managed drought condition: Genetic variability for key physiological traits in groundnut under managed drought condition - B N HARISH BABU; G CHANDRASHEKHARA; S K PATTANASHETTI (Journal of Oilseeds Research, 2020)
Drought is a major production constraint in rainfed groundnut. In the present study, genetic variability for relative water content (RWC) of leaf, membrane stability index (MSI), SPAD chlorophyll meter readings (SCMR) and percent wilted plants was assessed in 40 advanced breeding lines of groundnut under managed drought condition. Significant differences were noticed for key physiological traits. The RWC of leaf, MSI and percentage of wilted plants under drought showed high GCV, PCV, heritability coupled with high genetic advance over mean. The SCMR showed lower GCV and PCV but exhibited high heritability with moderate genetic advance over mean indicating the possibility to improve this trait by proper selection methods.